Ojibway plant taxonomy at Lac Seul First Nation, Ontario, Canada - Kenny, Mary Beatrice (2000)
The Ojibway (Anishinabe) of Lac Seul First N ation reside in the transition zone of the Great Lakes-St. Lawrence and southern Boreal Forest regions of northwestern Ontario, Canada. Hunting and gathering of certain animal and plant species remain a significant part of their livelihood. Although Lac Seul Ojibway are traditionally hunter-gatherers, there is a manipulation of the plant community in the cultivation of wild rice Zizartia aquatica L. beds and certain w ild medicinal plants. During the winter and summers of 1996-1997, a preliminary study was undertaken to collect plant taxonomic information in the Oji-Cree dialect of the community. Four Elders, fluent in the Oji-Cree dialect and who were knowledgeable of plant names, were interviewed. They were presented with plant material for identification. Five other Elders also contributed their knowledge about plants. Analysis of the taxonomic system follow ed Brent Berlin, with some exceptions. In Lac Seul folk plant taxonomy, there is no 'unique beginner' to correspond with Plantae. There are two Super Life-forms which include all vascular plants. This is the first use of the rank Super Life-form in ethnobotanical classification. There are eight named or covert Life-form taxa. Three of the Life-form taxa, characterized as 'medicinal roof, 'berry' and 'bark utility', are 'cultural' or utilitarian and overlap with the remaining Life-forms; 'conifer' (covert), 'angiosperm tree' (covert), 'herbs, ferns and fern allies', 'shrub' and 'moss'. As noted by Turner, Hunn and Johnson- Gottesfeld in other studies of non-agrarian indigenous groups, plant classification at Lac Seul reveals utilitarian identification which overlaps with morphological identification. A significant aspect of the data is the percentage of polytypic folk genera. Polytypic folk genera are usually about 18% of the total folk genera in horticultural groups and 2% of the total folk genera for foragers. At Lac Seul, the polytypic folk genera are 9% which shows a higher differentiation of folk genera than for most hunter-gathering people. Certain ubiquitous species have the same name at Lac Seul as in other Algonkian dialects ranging geographically from northern Saskatchewan to western Quebec.